Characteristics of adolescents living with HIV receiving care and treatment services in antiretroviral therapy clinics in Cambodia: descriptive findings from a cross-sectional study - Siyan Yi; Sovannary Tuot; Khuondyla Pal; Vohith Khol; Say Sok; Pheak Chhoun; Laura Ferguson; Gitau Mburu (BMC, 2018)
Abstract Background Adolescents living with HIV experience worse HIV care outcomes compared to adults, especially during transition from pediatric to adult care. However, data regarding adolescents are limited. This paper describes and compares characteristics of male and female adolescents living with HIV preparing for transition from pediatric to adult care in Cambodia. Methods This cross-sectional study was conducted in August 2016 among 328 adolescents aged 15-17, randomly selected from 11 antiretroviral therapy (ART) clinics. Data were collected using a structured questionnaire, and descriptive analyses were conducted to compare characteristics of male and female adolescents. Results Of total, 55.2% were male, and 40.8% were living with parents. Majority (82.6%) got HIV infection from their mothers. Overall, adolescents had received ART for an average of 8.4 years, and HIV care for 9.5 years. Additionally, 82.4% were on first line ART regimen. Mean CD4 count from the most recent test was 672 cells/mm3, and viral load was 7686 copies/mL. Overall, 95.6% were adherent to ART on Visual Analogue Scale. About half (50.7%) had never disclosed their HIV status to anyone, while the remaining had disclosed it to their siblings (24.2%), friends (13.0%), schoolteachers (2.4%), or other (5.8%). A fifth reported having had boy or girlfriends, but few (2.1%) had ever had sexual intercourse. Females were more likely to have been engaged in sexual intercourse, and none reported having used a condom in their last intercourse. Few participants reported having ever used tobacco (1.8%), or any kind of illicit drugs (0.9%), but almost a fifth (20.7%) had a history of alcohol use. The majority (82.1%) were aware that they were receiving ART. HIV-related knowledge was suboptimal among the sample. Conclusions This study provides a snapshot of immunological, virological, adherence, and disclosure outcomes that should be tracked during and following healthcare transition to evaluate the effectiveness of the transition program. Findings showed high ART adherence, low likelihood of disclosure outside of family circles, sub-optimal condom use, and poor knowledge of HIV. To provide individualized support for healthcare transition, pediatric and adult clinics need to ensure that these characteristics are taken into account.